Take-overs : their relevance to the stock market and the theory of the firm - Singh, Ajit (Cambridge [Eng.] University Press, 1971)
This is a two part publication which focuses on the economic characteristics of UK quoted industrial firms between the period 1948-54 and 1954-60. This second part focus on the firms that did not survive.
Continuation of Growth, profitability and valuation.
Includes bibliographical references: p. [167]-170.
lje 6/4/17
Loans
Keywords: Consolidation and merger of corporations; Stock exchanges; Great Britain